Infection dynamics of Enteromyxum leei (Myxozoa, Myxosporea) in culture water and its effects on cultured olive flounder, Paralichthys olivaceus (Temminck & Schlegel). Issue 9 (28th June 2021) - Sohn, Hanchang; Jin, Chang Nam; Kang, Bong Jo; Shin, Sang Phil; Lee, Jehee
Abstract: Enteromyxum leei is a causative agent of enteromyxosis, with a wide range of marine fish hosts. Recently, massive morbidity and mortality were caused by E. leei infection in cultured olive flounders in Korea. To reveal a relationship between E. leei abundance in culture water and the occurrence of parasite infection in host fish, we used a quantitative PCR assay targeting the 28S rDNA of E. leei in three fish farms (two where enteromyxosis had occurred and one where it did not) from April to November 2018. The gene of E. leei was detected at levels greater than 10 cells/L in the culture water where enteromyxosis occurred from July to September. Furthermore, 2 months after the detection in the water, the parasite gene (with more than 5, 000 cells per 100 mg) was detected in fish intestine samples. However, in the fish farms where enteromyxosis had not occurred, the E. leei gene was detected at <10 cells in culture water (1 L) and fish intestine samples (100 mg). The quantification method used in this research provides a baseline of the infection timeline in olive flounder to develop effective management practices.